Effect of Indocyanine Green Fluorescence Angiography on Anastomotic Leakage in Patients Undergoing Colorectal Surgery: A Meta-Analysis of Randomized Controlled Trials and Propensity-Score-Matched Studies - Tang, Gang; Du, Donglin; Tao, Jie; Wei, Zhengqiang (Frontiers in Surgery, 2022)
Background: Meta-analyses have demonstrated that indocyanine green (ICG) can effectively prevent anastomotic leakage (AL) after colorectal surgery. However, recent evidence from large randomized controlled trial (RCT) has suggested that ICG fluorescence angiography does not reduce the incidence of AL in colorectal surgery. This study was conducted to evaluate the value of ICG for the prevention of AL following colorectal surgery. Methods: Up to September 16, 2021, PubMed, Embase, China National Knowledge Infrastructure, Web of Science, Scopus, Cochrane Library, and VIP databases were searched for RCTs and propensity-score matched (PSM) studies evaluating the use of ICG for prevention of AL after colorectal surgery. Mean differences (MDs) or odds ratios (ORs) and 95% confidence intervals (CI) were calculated. Results: Twenty studies (5 RCTs and 15 PSM studies) with a total of 5125 patients were included. ICG did not reduce the reoperation rate (OR, 0.71; 95% CI, 0.38, 1.30), conversion rates (OR, 1.34; 95% CI, 0.65, 2.78), or mortality (OR, 0.50; 95% CI, 0.13, 1.85), but ICG did reduce the incidence of AL (OR, 0.46; 95% CI, 0.36, 0.59) and symptomatic AL (OR, 0.48; 95% CI, 0.33, 0.71), and reduced the length of hospital stay (MD, -1.21; 95% CI, -2.06, -0.35) and intraoperative blood loss (MD, -9.13; 95% CI, -17.52, -0.74). In addition, ICG use did not increase the incidence of total postoperative complications (OR, 0.93; 95% CI, 0.64, 1.35), postoperative ileus (OR, 1.26; 95% CI, 0.53, 2.97), wound infection (OR, 0.76; 95% CI, 0.44, 1.32), urinary tract infection (OR, 0.87; 95% CI, 0.30, 2.59), pulmonary infection (OR, 0.23; 95% CI, 0.04, 1.45), urinary retention (OR, 1.08; 95% CI, 0.23, 5.04), anastomotic bleeding (OR, 1.53; 95% CI, 0.27, 8.60), anastomotic stricture (OR, 0.74; 95% CI, 0.24, 2.29), or operative time (MD, -9.64; 95% CI, -20.28, 1.01). Conclusions: ICG can effectively reduce the incidence of AL, without prolonging the operation time or increasing postoperative complications in colorectal surgery.